Impact of oral health service expansion funding at health centers in the United States. (27th July 2020) - Nguyen, Vy; Daniel, Marlon; Joskow, Renée; Lu, Connie; Chen, Xiao; Zhou, Weihao; Lin, Sue; Sripipatana, Alek; Nair, Suma; Pourat, Nadereh
Abstract: Objectives: This study aims to assess the impact of Health Resources and Services Administration (HRSA) investment in oral health through the HRSA FY16 Oral Health Service Expansion (OHSE) funding on workforce, access, and quality in health centers (HCs) from 2015 to 2017. Methods: Analyses were conducted using data from the Uniform Data System from 2015 and 2017, and the 2015 Area Health Resource File. Change in indicators of oral health workforce, access, and quality of care by the receipt of OHSE funding received by HCs in 2016 were examined. Regression models for 1, 345 HCs were developed to conduct a difference‐in‐difference analyses of the comparative change from 2015 to 2017 in the dependent variables among OHSE and non‐OHSE awardees while controlling for confounders. Results: OHSE awardees showed a significant difference in the oral health workforce with a higher mean number increase by 0.6 full time equivalent (FTE) dentists, 0.4 dental hygienists, 1.1 dental assistants, and 2.3 for other dental staff compared to non‐OHSE awardees. Compared to non‐OHSE awardees, OHSE awardees showed a mean increase of 712 dental patients served who received 1, 402 dental visits, representing a 9‐percentage point increase in the percentage of HCs that had an oral health program and a 3‐percentage point increase in the ratio of dental patients to total patients. Conclusions: Funding dedicated to oral health service expansion in HCs may result in outcomes ranging from increasing workforce to reduction in access and financial barriers. Retrospective analysis demonstrated improved capacity for oral healthcare delivery attributable to HRSA support to HCs.